(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article provides general information about achromatic, chromatic, warm and cold, primary and secondary colors taught in color science, which is considered a branch of fine art, comments on colors, and for brush owners describes a wide range of knowledge and skills related to working with color in the creative process.